If it's not what You are looking for type in the equation solver your own equation and let us solve it.
21(-9x+9=0)
We move all terms to the left:
21(-9x+9-(0))=0
We add all the numbers together, and all the variables
21(-9x+9)=0
We multiply parentheses
-189x+189=0
We move all terms containing x to the left, all other terms to the right
-189x=-189
x=-189/-189
x=1
| 3x+14+2x-12=60 | | 3=-(1/9)u | | x6+8=-2 | | 5^9x-9=8^2x-5 | | 1/3x-5=-8 | | X(11+7)=2x(1+-8) | | a•6=20 | | 3=-(1/3)u | | -6r^2r=5 | | -3(g+5)=-12 | | (3x-11)+(2x+5)=180 | | 3=(-1/9)u | | 6x+26x-10=8(4x+10)* | | x²+8-12=0 | | 45.32+x=98.76 | | 12x/5=-36 | | 2+5.5k=18.43 | | –9f=–3(3f+18)+9 | | 304=-8(8a+2) | | 3(4x-1)=12-1 | | –4/5(9x–20)–3x=45 | | (x-24)=29-296 | | 15w^2+w=28 | | 7/29=$1.68/x | | x–15=2 | | 7a+1=-97 | | 7(h-89)=35 | | 304=8(8a+2) | | (x-24)-29=296 | | 3=-1/9u | | 15x+7=5x+37 | | 33-5x=17* |